First oncolytic virus approved for melanoma immunotherapy. (2nd January 2016) - Pol, Jonathan; Kroemer, Guido; Galluzzi, Lorenzo
ABSTRACT: On 2015, October 27th, the US Food and Drug Administration (FDA) has officially approved talimogene laherparepvec (T-VEC, also known as OncoVEX GM-CSF ) for use in melanoma patients with injectable but non-resectable lesions in the skin and lymph nodes. T-VEC (which is commercialized by Amgen, Inc. under the name of Imlygic®) becomes therefore the first oncolytic virus approved for cancer therapy in the US.